Reliability, Maintainability and Risk Practical Methods for Engineers including Reliability Centred Maintenance and Safety-Related Systems. - Smith, David J. (Burlington : Elsevier Science, 2011)
This book provides engineers with the safety and risk assessment tools and techniques they need to work effectively in any safety or reliability critical environment. These tools are primarily statistical. Where David Smith's book succeeds is by meeting the needs of an applied audience by setting these tools in the context of the design and operation of safety related processes and systems. Now in its Eighth Edition, this is regarded as the core reference in this field, and the success of its approach is reflected in the popularity of this standard work. It deals with all aspects of reliabilit.
Appendix 7 -- Fatality ratesAppendix 8 -- Answers to Exercises; Bibliography; Appendix 10 -- Scoring Criteria for BETAPLUS Common Cause Model; Appendix 11 -- Example of HAZOP; Appendix 12 -- HAZID Checklist; Appendix 13 -- Markov Analysis of Redundant Systems.
Keywords: Reliability (Engineering).; Industrial safety; Maintainability (Engineering); Civil engineering; Engineering; Electronic books